Renegotiation of Social Contracts by Majority Rule. - Dan Anderberg; Carlo Perroni (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
We consider renegotiation of social earnings insurance arrangements by majority voting in an economy where ex-ante identical individuals make unobservable private investments in education. We show that voting-based renegotiation can result in a higher expected level of investment in comparison to the case where social insurance is determined by an appointed social planner. We also find that, with voting-based renegotiation, the availability of costly ex-post information about private investment can help overcome commitment problems. These findings call into question the practice of using a representative-consumer approach when modelling dynamic policy problems in large economies.
Keywords: 330